2008
DOI: 10.1897/07-548.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil sorption and aquatic natural organic matter on the antibacterial activity of a fullerene water suspension

Abstract: The present study investigated the association of a C60 water suspension (nC6) with natural organic matter, present as a soil constituent or dissolved in the water column, and its effect on the antibacterial activity of nC60. Sorption of nC60 to soil reduced its bioavailability and antibacterial activity, and the sorption capacity strongly depended on the organic content of the soil. Adsorption of aquatic dissolved humic substances onto nC60 and possible subsequent reactions also were found to eliminate nC60 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 27 publications
8
73
2
1
Order By: Relevance
“…Both C 60 and nC 60 resulted in limited alteration to either the function or structure of microbial processes or communities (Tong et al, 2007). These findings are similar to those of Johansen et al (2008), and consistent with other investigations in which the bioavailability and antibacterial activity of nC 60 reportedly diminished following sorption to soil, with the overall sorption capacity dictated by the soil OM content (Li et al, 2008).…”
Section: Cnm Toxicity To Soil Microorganismssupporting
confidence: 87%
“…Both C 60 and nC 60 resulted in limited alteration to either the function or structure of microbial processes or communities (Tong et al, 2007). These findings are similar to those of Johansen et al (2008), and consistent with other investigations in which the bioavailability and antibacterial activity of nC 60 reportedly diminished following sorption to soil, with the overall sorption capacity dictated by the soil OM content (Li et al, 2008).…”
Section: Cnm Toxicity To Soil Microorganismssupporting
confidence: 87%
“…For example, dissolved organic matter can be critical in controlling metal bioavailability to aquatic organisms [27]. Conversely, humic and fulvic acids are also known to reduce the toxicity of ENMs [28,29] and slow the dissolution of metal-based ENMs [30]. Moreover, natural dispersants are usually not well characterized, and the properties of natural organic matter often used in ENM experiments, such as Suwannee River humic acid, may not be representative of the wide range of organic matter in different environments.…”
Section: Dispersing Agents and Solvent Controlsmentioning
confidence: 99%
“…Studies have shown that NPs undergo a series of chemical conversions, including chemical adsorption of toxic metal anions, complexation of organic molecules, and subsequent dissolution [41][42][43]. In addition, NP aging (weathering) affects dissolution and reactivity [13,44,45]. Previously, we reported that ZnO NPs undergo a dramatic physicochemical transformation with aging [22].…”
Section: Discussionmentioning
confidence: 97%